Bioinoculants-Natural Biological Resources for Sustainable Plant Production - Maitra, Sagar; Brestic, Marian; Bhadra, Preetha; Shankar, Tanmoy; Praharaj, Subhashisa; Palai, Jnana Bharati; Shah, M Mostafizur Rahman; Barek, Viliam; Ondrisik, Peter; Skalický, Milan; Hossain, Akbar (Microorganisms, 2021)
Agricultural sustainability is of foremost importance for maintaining high food production. Irresponsible resource use not only negatively affects agroecology, but also reduces the economic profitability of the production system. Among different resources, soil is one of the most vital resources of agriculture. Soil fertility is the key to achieve high crop productivity. Maintaining soil fertility and soil health requires conscious management effort to avoid excessive nutrient loss, sustain organic carbon content, and minimize soil contamination. Though the use of chemical fertilizers have successfully improved crop production, its integration with organic manures and other bioinoculants helps in improving nutrient use efficiency, improves soil health and to some extent ameliorates some of the constraints associated with excessive fertilizer application. In addition to nutrient supplementation, bioinoculants have other beneficial effects such as plant growth-promoting activity, nutrient mobilization and solubilization, soil decontamination and/or detoxification, etc. During the present time, high energy based chemical inputs also caused havoc to agriculture because of the ill effects of global warming and climate change. Under the consequences of climate change, the use of bioinputs may be considered as a suitable mitigation option. Bioinoculants, as a concept, is not something new to agricultural science, however; it is one of the areas where consistent innovations have been made. Understanding the role of bioinoculants, the scope of their use, and analysing their performance in various environments are key to the successful adaptation of this technology in agriculture.
Keywords: climate change mitigation; bioinoculants; negative impact; green revolution; agricultural sustainability